Falsehoods and facts about dietary sugars: a call for evidence-based policy. Issue 22 (16th December 2021) - Archer, Edward; Arjmandi, Bahram
Abstract: Sugar, tobacco, and alcohol have been demonized since the seventeenth century. Yet unlike tobacco and alcohol, there is indisputable scientific evidence that dietary sugars were essential for human evolution and are essential for human health and development. Therefore, the purpose of this analytic review and commentary is to demonstrate that anti-sugar rhetoric is divorced from established scientific facts and has led to politically expedient but ill-informed policies reminiscent of those enacted about alcohol a century ago in the United States. Herein, we present a large body of interdisciplinary research to illuminate several misconceptions, falsehoods, and facts about dietary sugars. We argue that anti-sugar policies and recommendations are not merely unscientific but are regressive and unjust because they harm the most vulnerable members of our society while providing no personal or public health benefits.